From Beirut to Jerusalem - Friedman, Thomas (New York Harper Collins Publishers, 1995)
A Second Edition of Thomas Friedman's stunning book, the first edition of which won the American National Book Award. 'If you're only going to read one book on the Middle East, this is it.' Seymour Hersh In this lucid, incisive and memorable book, acclaimed on both sides of the Atlantic, Friedman reaches deeper into the traumatic and complex recent history of the conflicts in the Middle East than any previous writer. For this new edition, Friedman has added a further two chapters that bring the book up to 1995 and the unfolding - and stalling - of the Middle Eastern peace process. From Beirut to Jerusalem is wonderully shrewd, surprisingly funny and indispensable to anyone seeking a fuller understanding of the political causes and psychological effects of the seemingly endless strife which besets this embattled region.
Include Index
Keywords: Middle East -- Politics and government -- Politics and government